Faktor-Faktor Yang Mempengaruhi Ekuitas Merek Pada Pengguna Mobile Banking Bank Syariah Indonesia - Anindita Imam Basri; Ika Desti Yuliana (JPS (Jurnal Perbankan Syariah), 2022)
This research aims to show the effect of trust, perceived quality, brand awareness, and brand loyalty on the brand equity of mobile banking users of Bank Syariah Indonesia in the Special Region of Yogyakarta. This research is a quantitative research using secondary data and primary data. The research sampling technique used purposive sampling. The questionnaire was distributed using google form with a sample size of 105 respondents. Data analysis used multiple linear regressions. The results showed that partially trust, brand awareness, and brand loyalty positively and significantly affect brand equity. Perceived quality has no significant effect on brand equity. Simultaneously has a significant effect. Trust, brand awareness, and brand loyalty can be used as factors influencing brand equity and can be used by Bank Syariah Indonesia in increasing the brand equity of mobile banking.